Rumours and Realities of Marriage Practices in Contemporary Samin Society - Arif Rohman (Humaniora, 2010)
Since the mid - 19th century the Samin people have made a contribution to resisting the Dutch colonial rule in rural Java through their non-violence movement and passive resistance (lijdelijk verset). History also notes that they have a unique culture and system of values which reflect their own local wisdom. However, many negative rumours have become widespread regarding this community. This article explores the marriage practices in Samin society and investigates how this society gives meaning to these marriage practices. It also examines whether the practice of 'virginity tests' and 'stray marriages' exist in contemporary Samin society.